Scale up study on production of biodiesel from jatropha crude oil - Ainul Nadirah, Izaharuddin (2010)
Scale up is a very important activity in designing new industrial plants especially in specialty or fine chemicals production. In this work, bench scale and pilot plant scale up factors are examined in producing biodiesel from Jatropha oil. The production of biodiesel in bench scale is compared to the pilot plant scale production. There are two processes involved in this work i.e. esterification process and transesterification process. The esterification process used H2SO4 as a catalyst while in transesterification process used NaOH as a catalyst. The ratio between Jatropha oil to methanol, the time reaction, and the temperature are similar in both scales. From the result, it was found that for bench scale and pilot plant scale, there are some differences in the value of the final yield. The difference value between the bench scale and pilot plant run was caused by several factors such as handling, operating conditions etc.